The Effect of Combining Foot Exercises and Neuromuscular Taping on Diabetic Foot Neuropathic Pain - Ilahude , Imran; Kristianto, Heri; Wibisono, Ahmad Hasyim; Blow, David (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Neuropathic pain in diabetic feet can affect patients' quality of life. This has an impact on sleep quality and daily activities. Neuromuscular taping (NMT) intervention and foot exercises can be therapeutic modalities for diabetic feet. A study on the combination of the two is needed. The research aimed to determine the effect of diabetic foot exercises and neuromuscular taping on diabetic foot neuropathic pain. The research employed a quasi-experimental design with a crossover design approach. The sample included 24 people recruited using the purposive sampling method. The sample was divided into two groups: the control group and the intervention group. The control group received foot exercises only, while the intervention group received a combination of foot exercises and neuromuscular taping. The washout period was carried out for one week. Neuropathic pain scores were measured using the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS). Data were analyzed using the Wilcoxon test. The study's results showed that the mean change in neuropathic pain scores in the control group with a median (min-max) value was -2.00 (-8 - 0). In the intervention group, the mean change with a median (min-max) value was - 7.50 (-10). - 0). There was a significant reduction of diabetic foot neuropathic pain in the control and intervention groups with a p-value of 0.000 (α<0.05). In conclusion, a combination of foot exercise and neuromuscular taping interventions can be an option for managing diabetic foot neuropathic pain